Pelatihan Diversifikasi Olahan Jeruk dan Bunga Telang Menjadi Permen Gummy Alami sebagai Produk Pangan Sehat - Raden Roro Ariessanty Alicia Kusuma Wardhani; Antoni Pardede; Dewi Lesmanawati; Ana Sofia Herawati; Fanlia Adiprimadana Sanjaya; Miftahul Huda; Chandra Halim (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Jelly candies available on the market generally contain synthetic food additives, such as preservatives, artificial sweeteners, and artificial colorings, which may pose health risks, particularly to children, when consumed excessively. This community service program aimed to increase participants' knowledge about the potential hazards of synthetic food additives, provide practical training on producing healthy jelly candies using natural ingredients, and encourage the development of safe, home-based food products with economic value. The program targeted 22 members of the Family Welfare Empowerment (PKK) group in North Alalak Village. The implementation consisted of preparation, educational counseling, demonstrations and hands-on practice in making jelly candies from oranges and butterfly pea flowers (Clitoria ternatea L.), followed by evaluation using pre-test and post-test assessments. Oranges were selected for their natural flavor and high vitamin C content, while butterfly pea flowers were chosen for their anthocyanin content, which functions as a natural antioxidant. The results showed a high level of participant enthusiasm and a significant improvement in knowledge, as evidenced by the comparison of pre-test and post-test results. Participants were also able to independently prepare healthy jelly candies using natural ingredients. This program successfully enhanced the knowledge and skills of PKK members in processing natural food products while creating opportunities to develop healthy jelly candies as safe snacks for children and as potential home-based business products.